2018
DOI: 10.1002/vnl.21623
|View full text |Cite
|
Sign up to set email alerts
|

Polylactide/organoclay nanocomposites: The effect of organoclay types on the structure development and the kinetic of cold crystallization

Abstract: Polylactide (PLA)/organoclay composites were prepared by melt compounding with 4 phr of two different types of organoclays (cloisite 20A and cloisite 30B). Structure development and nonisothermal kinetic of cold crystallization of PLA/organoclay nanocomposites were examined by using of X‐ray diffraction technique, transmission electron microscopy, melt viscoelastic measurements, and differential scanning calorimetry. XRD results demonstrated that the melt intercalation of PLA chains into the cloisite 30B and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 39 publications
2
5
0
Order By: Relevance
“…The XRD patterns, shown in Figure 3a, reveal the structure of MMT clay (Cloisite 30B) and clay in the nanocomposites. The MMT clay exhibits a 2θ at 4.8 degree characterized by an interlayer distance (d 001 ) of 1.8 nm, which is in line with the previous work [33][34][35][36]. By monitoring the position, shape, and intensity of the basal reflections from the distributed clay layers, the nanocomposite structure (intercalated or exfoliated) could be identified.…”
Section: Nanocomposites Of Pla Block Copolymer and Claysupporting
confidence: 88%
“…The XRD patterns, shown in Figure 3a, reveal the structure of MMT clay (Cloisite 30B) and clay in the nanocomposites. The MMT clay exhibits a 2θ at 4.8 degree characterized by an interlayer distance (d 001 ) of 1.8 nm, which is in line with the previous work [33][34][35][36]. By monitoring the position, shape, and intensity of the basal reflections from the distributed clay layers, the nanocomposite structure (intercalated or exfoliated) could be identified.…”
Section: Nanocomposites Of Pla Block Copolymer and Claysupporting
confidence: 88%
“…By comparing PLA films filled with C20A and DCNP at an equal concentration (i.e., 3 wt %), it was observed that the shoulder is more intense for C20A, which could be attributed to better delamination of DCNP in the PLA matrix compared to that of C20A. The interaction of ester functional groups in PLA chains with polar substituents of MB can enhance the compatibility of DCNP with PLA and results in more uniform dispersion of DCNP compared to that of C20A. Visual investigation of DCNP dispersion in PLA was performed by high-resolution transmission electron microscopy (HRTEM) to precisely depict the dispersion state and support XRD findings. The micrograph of PLA–DCNP3 at low magnifications (Figure A) only showed random dispersion of variously sized DCNP tactoids in the PLA matrix.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the mechanical properties of polymer nanocomposites are a function of the nanoparticle dispersion state in the matrix and the extent of interactions between the polymer chains and nanoparticles. 17,25 Accordingly, the better mechanical properties of PLA/ZnO(1) can be attributed to the fact that the stress transfer at the interface between matrix and nanofiller with rod or cylindrical morphology is more effective than the spherical morphology. 33 As was stated, all of the nanocomposites filled with both ZnO and TiO 2 (PLA/ ZnO/TiO 2 ) contain a total of 7 wt%.…”
Section: Morphological Analysismentioning
confidence: 99%
“…16,19 ZnO is also a non-toxic and multi-functional mineral nanoparticle with high chemical stability, high catalytic activity, considerable ultraviolet light absorption, and antibacterial properties which is recognized as a safe material by the US Food and Drug Administration. 6,[13][14][15][16][17][20][21][22] Searching the literature, numerous publications are available regarding the PLA/ZnO and PLA/TiO 2 nanocomposites and their property improvements in terms of dispersion state, 23 mechanical, [17][18][19] thermal, 10,24,25 optical, 10,26 and antibacterial 16,27 properties. For instance, Therias et al 28 investigated how light affects PLA/ZnO nanocomposite films prepared by melt extrusion.…”
Section: Introductionmentioning
confidence: 99%